Demontrasi Endorphin Massage pada Ibu Hamil Mengurangi Nyeri Persalinan Wilayah Kerja Puskesmas Pintu Padang Kecamatan Batang Angkola Tapanuli Selatan - Sri Juwarni; Irwan Batuabara; Herawati Harahap; Rika Apripan; Ramlan Ramlan (Lembaga Pengembangan Kinerja Dosen, 2025)
Community service has been carried out by the service team involving students from the Padangsidimpuan Midwifery Study Program, Poltekkes Kemenkes Medan. The community service activities carried out were to provide counseling and demonstrations about Endorphine massage which is a light touch or massage therapy that is quite important to be given to pregnant women, in the time leading up to and during childbirth. This massage can stimulate the body to release endorphin compounds which are pain relievers and can create a feeling of comfort. Endorphins in the body can be triggered through various activities, such as deep breathing and relaxation, and meditation. Endorphine massage should be done to pregnant women who are 36 weeks pregnant. Because endorphin massage can stimulate the release of the hormone oxytocin which can trigger the labor process (Kuswandi, 2014). This Community Service aims to demonstrate endorphin massage to reduce pain in mothers giving birth in the first stage in the Pintu Padang Health Center work area, South Tapanuli Regency. Target pregnant women in the third trimester, young couples, Participants 40, endorphin massage is expected to be implemented in the management of the first stage to reduce pain and speed up the labor process. The results of this community service are an increase in knowledge of 50% and skills of 87% about endorphin massage correctly applied when pregnant women later undergo the labor process. This community service is carried out in collaboration with partners used as the location of this activity, namely Kalurahan Pintu Padang, Batang Angkola District, South Tapanuli Regency and Health Cadres, Village Midwives at the local Health Center. This activity received a positive response from local participants, and as a follow-up, it can be carried out by Health Cadres and midwives at the Health Center to monitor the skills that have been obtained when pregnant women are in the labor process that will be undergone